Umckalin Promotes Melanogenesis in B16F10 Cells Through the Activation of Wnt/β-Catenin and MAPK Signaling Pathways - So-Yeon Oh; Chang-Gu Hyun (Applied Biosciences)
Melanogenesis is regulated by melanogenic enzymes such as tyrosinase (TYR), TRP-1, and TRP-2, whose expression is controlled by the microphthalmia-associated transcription factor (MITF). Various signaling pathways, including cAMP/PKA, MAPK/ERK, Wnt/β-catenin, and PI3K/Akt, are involved in this process and have been a focal point of research for treating pigmentation disorders. However, developing effective therapies for conditions like vitiligo remains a significant challenge. In this study, the effects of umckalin on melanogenesis and its molecular mechanisms were investigated using B16F10 cells, a mouse melanoma cell line widely used as a model for melanin production studies. B16F10 cells produce melanin via melanosomes and express key melanogenic enzymes such as TYR, TRP-1, and TRP-2, making them a reliable model system. Our findings demonstrate that umckalin promotes melanogenesis in a concentration-dependent manner by upregulating TRP-1 expression and activating the MITF signaling pathway. Additionally, umckalin modulated key signaling pathways, including GSK3β/β-catenin and MAPK, to enhance melanogenesis. In conclusion, umckalin enhances melanogenic enzyme activity by activating critical signaling pathways, thereby promoting melanin synthesis. These findings suggest that umckalin could be a promising candidate for developing therapeutic agents for pigmentation disorders such as vitiligo. Further studies are required to explore its mechanisms and clinical applications in greater detail.